Labeling and Patient Knowledge of Dispensed Drugs as Patient Care Indicators in Adulala Health Center Outpatient Pharmacy, Adulala, Ethiopia - Bikila Midaksa, Fanta Gashe, Messay Wolde-Mariam Anshebo, Raghavendra Yarlagadda (Journal of Applied Pharmaceutical Science, 2015)
Background: labeling and knowledge of dispensing drug is important for the patient to identify the contents and to ensure that they have clear and concise information about the use of the dispensed drug. Lack of this may lead the patient to incorrect use, which in turn results in an adverse effect. So the present was undertaken to assess the labeling and patient knowledge of dispensing drugs in Adulala Health Center outpatient pharmacy, Adulala, East Shoa, Ethiopia.Method: A cross sectional, prospective study was done by examining previously prepared a checklist to gather information from each package of dispensing drugs to patients and exit interview done with patients to assess their knowledge of the dispensed drug at Adulala Health Center Outpatient Pharmacy from January 23 to February 7, 2014. The data were analyzed by using statistical software package SPSS 16.0.Results: A total of 302 patients was studied of which majority (62.6%) of them were females and 38.2% of the patients were in the age group of 21-45. All the patients were aware of the dose and a majority (79.06%) of them about frequency. The labeling pattern of dispensing drugs attributes 100% in case of name, strength and expiry of the drug. Patient name was written in only 4.7% of the dispensed drugs. Out of a total 554 dispensed drugs most (46.93%) of them were dispensed for chemotherapeutic to a majority (192) of the patients of 21-45 age groups. Sex has no association with patient knowledge on dosage, frequency, and duration (p-value=0. 423, 0.630, 0.115) respectively.Conclusion: The study depicts that dispensed drugs had poor labeling. Educational level and patient age have a strong association with patient knowledge of dispensing drugs whereas sex has no association with patient knowledge. Dispensing time was short. Not all prescribed medications are dispensed.
Keywords: Labeling, Dispensed Drugs, Patient Care Indicators, East Shoa, Ethiopia.